(3JfXje h GOGQI GdYdGbGJ GdYGeI (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3GdYedjI GdJNWjWjI aj eVeGQ GdYdGbGJ GdYGeI , JfXje fTGWGJ GdYdGbGJ GdYGeI, GdJhLjg h GdbjGOI h GdGJUGd aj eVeGQ GdYdGbGJ GdYGeI GdaGYdI , GdQbGHI Ydi fTGWGJ GdYdGbGJ GdYGeI (B.s
(3eQGLY U(B.241s
Keywords: (3GdGJUGds; (3GdGOGQIs; (3GdJNWjWs; (3GdQbGHIs; (3GdYdGbGJ GdYGeIs